Theoretical Perspectives on Psychometric Assessment as a Strategic Mechanism in Personnel Selection and Recruitment - Kenku, Akeem A.; Yahaya, Isah; Uzoigwe, Tobechi L.; Buba, Jummai Hanna (NIU Journal of Social Sciences; Vol 12 No 1 (2026): NIU Journal of Social Sciences, Vol. 12 No. 1, March 2026DO - 10.58709/niujss.v12i1.2446, 2026)
Psychometric testing has gained prominence as an objective and standardized tool for informing selection decisions, limited scholarly work has integrated its use within broader strategic human resource management (SHRM) frameworks. This paper examines the strategic role of psychometric assessment in personnel selection and recruitment through a synthesis of established theoretical perspectives. The study adopts a qualitative theoretical methodology, drawing exclusively on secondary data from peer-reviewed journal articles, theoretical models, and existing empirical studies in organizational psychology, human resource management, and decision-science literature. Findings indicate that the strategic value of psychometric assessment can be explained through multiple theoretical lenses. Human Capital Theory positions psychometric tools as mechanisms for identifying and developing high-value human resources. Person–Environment Fit Theory reinforces the role of assessments in achieving optimal alignment between candidate attributes and job requirements. Decision-Making Theory highlights how psychometric instruments reduce cognitive biases and enhance the consistency of hiring decisions. Meanwhile, the Resource-Based View and Strategic HRM Theory conceptualize psychometric systems as organizational capabilities that provide competitive advantage when integrated into long-term talent strategies. The study concludes that psychometric assessment functions not merely as an evaluative tool but as a strategic mechanism that supports workforce planning, enhances decision quality, and contributes to sustainable organizational performance. The paper recommends that organizations adopt a multi-theoretical approach when designing selection systems, invest in assessor training to ensure proper test administration and interpretation, and consistently evaluate the fairness, relevance, and predictive validity of instruments used. Future research should empirically test the integrated theoretical model proposed in this study and explore contextual variations across industries and cultures. Keywords: Theoretical Perspectives, Psychometric Assessment, Strategic Mechanism, Personnel Selection, Recruitment